PENERAPAN PERATURAN MENTERI HUKUM DAN HAK ASASI MANUSIA REPUBLIK INDONESIA NOMOR 10 TAHUN 2020 DALAM PELAKSANAAN ASIMILASI NARAPIDANA DAN ANAK KARENA COVID-19 (Studi di Lembaga Pemasyarakatan Kelas I Malang) - Ramadhani Agung Nugraha (Dinamika, 2021)
The theme above is motivated by the government's policy to provide an assimilation program at home for prisoners and children in the midst of the COVID-19 pandemic. Assimilation is given as a prisoner's right after fulfilling the requirements in the applicable law. Assimilation is the development of adult and child prisoners by allowing them to mingle in the community. In the midst of the corona pandemic, prisons are a place of risk because many prisons are unfit for habitation due to overcapacity so that the sosial distancing policy is impossible to implement. The expenditure of prisoners and children through the assimilation program at home is a follow-up to the United Nations call that urges governments in the world to release low-risk prisoners.Based on the above background, the author raises several problems as follows: 1) How is the application of the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 10 year 2020 in the implementation of assimilation for inmates and children due to COVID-19 at the Class I Prison of Malang ?; 2) What are the obstacles faced in implementing Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 10 year 2020 in the implementation of assimilation for prisoners and children due to COVID-19 in Class I Prison of Malang? and 3) What are the efforts made to overcome the obstacles in the application of the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 10 year 2020 in the implementation of assimilation for prisoners and children due to COVID-19 at the Class I Prison of Malang?This research is a qualitative descriptive study with a sociological juridical approach. Primary data collection was carried out by means of interviews, while secondary data was obtained from literature studies and documents related to research problems. The results of the research were analyzed inductively to answer the issues that became the main problem.The results showed that the release of prisoners and children through the assimilation program due to COVID-19 in Class I Prison of Malang was in accordance with the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 10 year 2020. The obstacles encountered in implementing Minister Regulation Number 10/2020 are: a) administrative constraints; b) difficulty in supervising prisoners and children who are assimilated due to COVID-19; c) prisoners do not have a guarantor; d) prisoners take advantage of the assimilation program to ask for extra money from the family; e) public doubts about accepting back convicts who are free of assimilation due to COVID-19; and f) the prisoner repeats the crime after being free of assimilation due to COVID-19. Efforts to be made to overcome obstacles are: a) coordinating with Courts and Prosecutors; b) carry out control of prisoners and children who are free of assimilation related to COVID-19; c) coordinate with BAPAS Malang or BAPAS where prisoners live for prisoners who do not have a guarantor; d) socializing and motivating prisoners and children who will undergo assimilation at home; e) disseminating information through social media about the absence of fees for obtaining an assimilation program due to COVID-19; and f) coordinating with the Correctional Center, the Attorney General's Office and the Police, and the Kelurahan where each prisoner and child lives free of assimilation related to COVID-19. Keywords: Assimilation, Prisoners, COVID-19, Penitentiary